GALERY WALK DALAM AKTIVITAS BELAJAR: PENELITIAN TINDAKAN KELAS DI MADRASAH IBTIDAIYAH - Wawan Setiawan; Hani Nuraisah (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2018)
This study aims to determine the effect of the application of the Gallery Walk model to improve student learning activities on art subjects of ornamental motifs in 5th grade MI Al-Manar Cianjur. This research uses classroom action research method consisting of two cycles, each cycle there are two actions with the stages of activity planning, action, observation, and reflection. The results of the study: for cycle 1 and cycle 2 there are two actions, then the results of both actions are accumulated. Based on the data analysis, the result of the research shows that there is influence from the application of Gallery Walk method to the improvement of student learning activity seen from the percentage of measurement of pre cyclical learning activity of 28.07% with low criterion. Cycle 1 of 62,6% with a good criterion, while cycle 2 equal to 83,3% with a very good criterion. Based on the findings it can be seen that the implementation of Gallery Walk can improve student learning activities on subjects SBK subject of decorative motif type.